Borazarenes and borazoles. Flourescence spectrometry and quantum efficiencies in relation to slow neutron counting - Rojo, Enrique Aldo (1964)
Fil: Rojo, Enrique Aldo Comisión Nacional de Energía Atómica; Argentina